LOYALITAS PELANGGAN BERBASIS PEMASARAN DI SMPN 3 SATU ATAP KARANGSAMBUNG KEBUMEN - Ratna Marwati Ekasari (UPAJIWA DEWANTARA: Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2017)
Abstract This study aims to know the influence of promotion and facilities learned againsts the studentâ€™ satisfaction and consumers loyality in Junior high school 3 Satu Atap Karangsambung. The instruments use SPSS 17.0. and smart PLS 3.0. The subjects of this study is 53 student. The results of research show that Promotion and facility influence positively but not significant against the satisfaction. Promotion and facility influence positively but not significant to consumers loyality. The more influence of loyality are mediation that showed with the value coefficient as 0,243 or 24,3%. The result of total effect is promotion influence directly againts loyality as 0.286, the extent of influence of variables loyality is mediation with coefficient determination R Square 0,007 and the results of total effect as 0,279, while the variable learned facility influence indirectly toward loyality as 0,356, by mediation of consumer satisfaction as 0,008 and the result of total effect as 0,364.Â Keyword: Promotion,Facilities,Loyality Consumer Satisfaction